2002
DOI: 10.1007/s00101-002-0369-7
|View full text |Cite
|
Sign up to set email alerts
|

Moderne CT-Diagnostik des akuten Thorax- und Abdominaltraumas

Abstract: Whole body multislice-CT used as primary diagnostic tool in the management of polytraumatized patients allows for a fast, accurate and comprehensive diagnostic work-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 37 publications
1
31
0
10
Order By: Relevance
“…Improvement in computed tomography (CT) technology has led to the introduction of multislice CT in early trauma diagnostics [9][10][11][12][13]. Despite the implementation of trauma centers and trauma management concepts in the 1980s and 1990s, delays in diagnosis in early trauma care with underestimations of injury severity and consecutive delays in surgery still occur [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in computed tomography (CT) technology has led to the introduction of multislice CT in early trauma diagnostics [9][10][11][12][13]. Despite the implementation of trauma centers and trauma management concepts in the 1980s and 1990s, delays in diagnosis in early trauma care with underestimations of injury severity and consecutive delays in surgery still occur [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by recent technical improvements in CT scanner hard-and software delivering high-quality images of various body parts within a short time [6][7][8][9][10]. While several studies so far have demonstrated the technical feasibility of whole-body CT introducing various protocols and contrast media application techniques [2,11,12], the exact role and clinical value of a whole-body CT in terms of patient outcome as compared to a CT of dedicated body regions is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Zeitverzögerungen bei der Anlage des Katheters durch unerwartet schwierige Verhältnisse in der täg-lichen Praxis werden regelhaft beobachtet [7]. Demgegenüber liegen zahlreiche Arbeiten vor, die den Nutzen einer möglichst zeitnahen MSCT-Diagnostik im Rahmen der Schockraumversorgung belegen [1,4,9,14,15,18,20,28] …”
Section: Katheteranlageunclassified